Resilience and Sustainable Transportation Systems - Qiao, Fengxiang; Bai, Yong; Lin, Pei-Sung; Chien, I-Jy Steven; Zhang, Yongping; Zhu, Lin (American Society of Civil Engineers, 2020)
Proceedings of the 13th Asia Pacific Transportation Development Conference, held in Shanghai, China, May 27-30, 2020. Sponsored by the International Chinese Transportation Professionals Association, Shanghai University of Engineering Science, and the Construction Institute of ASCE.This collection contains 86 peer-reviewed papers on the construction, management, and maintenance of sustainable transportation systems.Topics include: transportation planning and systems development; infrastructure design and construction; transportation systems management and maintenance; multi-modal systems; urban railway planning and management; intelligent maintenance technologies for rail transit systems; rail noise and vibration control; sustainability and environmental and public health; and autonomous and connected vehicles.This proceedings will be of interest to practitioners and researchers addressing the design, construction, and maintenance challenges of advanced transportation systems.
Keywords: Intelligent transportation systems -- Congresses.; Railroads -- Congresses.; elektronické knihy; electronic books